How Do Science Content Misconceptions Occur in Primary School Teachers with Teaching Certificates? - Zulfianto, Muhammad Rais; Abduh, Muhammad (Mimbar Sekolah Dasar, 2023)
Misconceptions are understandings of concepts that are not in accordance with scientific concepts. Teachers have the potential to experience misconceptions and misconceptions that occur in teachers can result in students also experiencing misconceptions. Research that examines science misconceptions in elementary school teachers is still rare, so there is a need for research examining science misconceptions in elementary school teachers, especially in elementary school teachers who are certified educators. Therefore, this study aims at determining whether science misconceptions occur in elementary school teachers with teaching certificates or not and how much misconceptions are experienced and the misconceptions occurred. This study employs descriptive quantitative by involving 17 certified elementary school teachers who are classroom teachers teaching several subjects in elementary schools including science subjects. Data collection was done by conducting a four tier misconception diagnosis test and the result was analyzed using by referring to four tier test concept developed by various researchers. The findings indicated that primary school teachers possessing teaching certificates exhibited science misconceptions at a rate of 22%, placing them in the low category of scientific understanding at 66%. Despite the relatively low occurrence of misconceptions, it is advisable for certified primary school teachers to further enhance their grasp of the concepts they impart to prevent any potential hindrance to the learning process.